Educational evaluation for the achievement of learning standards in public school students, 2018 - Valdiviezo Vasconsuelo, Mercedes Milagros (2019)
The evaluation of learning was a highly studied subject for several years; however, there were some gaps and it was not given the proper importance in the teaching-learning process or its fundamental role for better learning achievements in students (learning standards) particularly in the use of written language. Therefore, the objective of the present study was to analyse the relationship between the evaluation of learning outcomes by the teacher and the achievement of standards of production of texts. The design of the study was non - experimental - transactional - correlational, two questionnaires were prepared and two rubricsvalidated through pilot test and expert judgement. The sample was composed by the secondary level students and teachers of communication of two public schools. The study concludes that there is a strong correlation between both constructs